A importância dos níveis séricos de vitamina D em pacientes lúpicos e na menopausa - Franchini, Cássia de Fátima Monteiro (2017)
This is an observational, cross-sectional retrospective study to evaluate the 25- hydroxyvitamin D (25(OH)D) levels in patients with Systemic Lupus Erythematosus (SLE) and determine the relationship between menopause and levels of vitamin D. We evaluated the records of patients treated between lupus 2010-2015 in private health care rheumatology city of Maringa-PR. It was observed the first dose of vitamin D each patient and the following characteristics: gender, age, disease duration, clinical manifestations of SLE, the presence of some autoantibodies (ANA, Anti-Sm, Anti-DNA) and menopause. The vitamin D deficiency was defined as serum 25(OH)D <30 ng / ml. Of the 186 patients evaluated, 127 had their certain level of vitamin D. The average vitamin D levels were 29.5 ± 8.92 ng / dl and 64 SLE patients had hypovitaminosis D. The mean serum levels of 25 (OH) D in vitamin D deficient patients was 23.37 ± 5 29 ng / ml in those without loss was 36.73 ± 5.24 ng / ml (p = 0.0001). It was demonstrated statistically higher prevalence (p = 0.0450) low vitamin D in women 62 (96.88%) compared to men 2 (3.13%). It was observed that vitamin D levels were statistically lower in postmenopausal women with SLE (p = 0.0005), average of 25.78 ng / ml against 31,55ng / ml in non-menopausal women with SLE. There was no association between hypovitaminosis D and the clinical parameters of the disease and laboratory studies. It was concluded, therefore, that vitamin D deficiency was higher in women than in men with SLE mainly in SLE in menopause and emphasizes the need for further research to better assess the relationship between vitamin D levels and menopause in SLE patients, emphasizing the importance of determination of serum 25(OH)D in all patients with this disease.